Design of an ice hockey stick test machine - McQueen, M.; McPhee, J. (The Engineering of sport 7, Volume 2, 2008)
With the introduction of one-piece composite ice hockey sticks in the early 21st Century, renewed attention has been drawn to hockey stick design, specifically with respect to durability. While one-piece composite ice hockey sticks have provided a performance Upgrade over their wood and aluminum predecessors, at least anecdotally, these sticks break far more frequently — very frequently during the slapshot. The failure occurs either at the connection between the blade and shaft or along the shaft itself, due to the large bending loads during the shot. The objective of this work is to create a system that dynamically tests hockey sticks in a repeatable manner to reduce the experiment variability associated with human testing. A motion analysis of the slapshot by an experienced player reveals that the motion of the stick is mainly two-dimensional during the period when it is subjected to large bending loads by the ice surface. Based on this, we synthesize a four-bar mechanism with a coupler curve that matches the required stick trajectory. A literature and patent search confirms this machine as an original design. Key words: Hockey, Stick, Slapshot, Testing, Machine Design.